Schooling and political activism in the early civil rights era - Daniel Aaronson; Mark Borgschulte; Sunny Liu; Bhashkar Mazumder (Federal Reserve Bank of Chicago, 2024)
Does education lead to political engagement? The empirical literature is mixed. Theory suggests economic context matters. Individuals unable to take advantage of education in the labor market are more likely to engage in political activity. We find support for this channel during the rapid expansion of NAACP branches in the South around WWII. Branch growth was stronger where Black workers were denied returns to schooling due to Jim Crow occupational discrimination. We further show that a pre-1931 large-scale school construction program caused greater NAACP activity during the 1940s and 1950s when many former students were in their prime working years.
Keywords: 330; education; human capital; social returns to education; NAACP; Rosenwald Schools; civil rights; civil rights movement; political participation